2008
DOI: 10.1007/s00431-008-0812-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute febrile neutrophilic dermatosis (Sweet’s syndrome) in childhood and adolescence: two new patients and review of the literature on associated diseases

Abstract: Sweet's syndrome should be considered in differential diagnosis of prolonged fever with cutaneous involvement. As most cases of pediatric Sweet's syndrome are associated with other diseases we suggest careful screening and monitoring of these patients especially concerning malignant/premalignant diseases, immunodeficiencies, cardiovascular involvement, autoimmune diseases, and drug associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 55 publications
0
63
0
7
Order By: Relevance
“…Se han descrito tres escenarios clínicos en los que se presenta el SS: clásico o idiopático, paraneoplásico e inducido por drogas (7) . En pediatría se ha descrito hasta un 45% de casos idiopáticos, posterior a infecciones gastrointestinales o respiratorias transitorias, un 30% asociado a condiciones inflamatorias crónicas y un 25% de los casos paraneoplásicos, siendo la mayor asociación con leucemia mieloide aguda, osteosarcoma y síndrome mielodisplásico (4,6,10,11) . Debido a estas asociaciones con diversas patologías se han propuesto esquemas de tamizaje de patologías asociadas al SS, que incluye aspectos clínicos como medición de presión arterial, pruebas de laboratorio básico: Hemograma-VHS, LDH y ácido úrico, además de detección de VIH, ANA y niveles de inmunoglobulinas séricas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se han descrito tres escenarios clínicos en los que se presenta el SS: clásico o idiopático, paraneoplásico e inducido por drogas (7) . En pediatría se ha descrito hasta un 45% de casos idiopáticos, posterior a infecciones gastrointestinales o respiratorias transitorias, un 30% asociado a condiciones inflamatorias crónicas y un 25% de los casos paraneoplásicos, siendo la mayor asociación con leucemia mieloide aguda, osteosarcoma y síndrome mielodisplásico (4,6,10,11) . Debido a estas asociaciones con diversas patologías se han propuesto esquemas de tamizaje de patologías asociadas al SS, que incluye aspectos clínicos como medición de presión arterial, pruebas de laboratorio básico: Hemograma-VHS, LDH y ácido úrico, además de detección de VIH, ANA y niveles de inmunoglobulinas séricas.…”
Section: Discussionunclassified
“…Debido a estas asociaciones con diversas patologías se han propuesto esquemas de tamizaje de patologías asociadas al SS, que incluye aspectos clínicos como medición de presión arterial, pruebas de laboratorio básico: Hemograma-VHS, LDH y ácido úrico, además de detección de VIH, ANA y niveles de inmunoglobulinas séricas. Se sugiere también la realización de un ecocardiograma y en caso de dolor óseo, estudio de imágenes, radiografía simple y/o resonancia magnética en caso de alta sospecha clínica (10) . En niños existen escasos casos inducidos por drogas, los que se han asociado a factor estimulante de colonias de granulocitos, ácido transretinoico, cotrimoxazol y azatioprina (8) .…”
Section: Discussionunclassified
“…8 Malignancy associated SS was seen in 23% of the patients which is comparable to study published by Abbas et al 9 Females outnumbered males in our study which is similar to that reported by Abbas et al None of the patients belonged to the pediatric age group which is in contrast to the frequency reported in the literature (5%). 10 Sweet's syndrome has been reported in association with both hematologic malignancies and solid organ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of Sweet's syndrome in children and adolescents by Hospach et al [5] in 37 malignancies and drugs account for 58 and 8 % of reported cases, respectively. Because AML and G-CSF are both common causes of Sweet's syndrome, it can be difficult to distinguish which one is responsible for Sweet's syndrome.…”
Section: Discussıonmentioning
confidence: 99%